HLA-B5/51 GENOTYPE: AN ASSOCIATION WITH THE CLINICAL MANIFESTATIONS OF BEHCET’S DISEASE - Z. S. Alekberova; F. I. Izmailova; I. A. Guseva; L. N. Denisov; S. I. Glukhova; T. V. Popkova (Научно-практическая ревматология, 2015)
Objective: to estimate the contribution of HLA-B5/51 genotype to the clinical manifestations and risk of Behcet’s disease (BD) in two ethnic groups.Subjects and methods. 146 BD patients fulfilling the International Criteria for BD (ICBD) were divided into two ethnic groups: 1) 86 patients from Dagestan (representatives of 8 ethnic nationalities in this region) with mean age 30.7±9.6 years; disease duration – 8.8±10.1 years; 2) 60 ethnic Russian patients, nonresidents of Dagestan with mean age 32.9±11.1 years; disease duration – 11.2±10.1 years. All patients were examined at the V.A. Nasonova Research Institute of Rheumatology in 1990 to 2014. HLA class I antigens were typed by a microlymphocytotoxic technique using a Gisans anti-leukocyte sera kit (Saint Petersburg).Results. HLA-B5/51 was detected in 87 (59.6%) patients, much more often in men than in women (70 and 38%, respectively; p<0.01). Genital ulcers and erythema nodosum were significantly more common in HLA-B5/51-positive Dagestani (87.3 and 57%) than in HLA-B5/51-negative ones (56.5 and 26%; p=0.0019 and р=0.01; respectively). There were no significant differences in these signs in the Russian group of patients with BD depending on the presence of this allele. In HLA-B5/51-positive male Dagestani patients with BD, the risk of erythema nodosum was twice as high as that in HLA-B5/51-negative patients (p=0.054). In HLA-B5/51 female Dagestani carriers, the risk of genital ulcers and generalized uveitis proved to be 3.5 (p=0.057) and 2.7 times higher than that in HLA-B5/51 noncarriers. Frequency of HLA-B5/51 was 73.2% among the Dagestanis and 40% among the Russians. Furthermore, this investigation revealed HLA-B5/51 carriage mainly in the male BD patients. Therefore, in addition to ethnicity, gender should be borne in mind when analyzing the clinical associations with HLA-B5/51.